BLADE turbo gradient- and spin-echo in the assessment of sinonasal lesions: a comprehensive comparison of image quality in readout-segmented echo-planar imaging. (October 2022) - Geng, Yue; Shi, Yiqian; Chen, Wei; Tang, Zuohua; Zhang, Zhongshuai; Zhou, Kun; Sha, Yan
Background: A two-dimensional turbo gradient-echo and spin-echo diffusion-weighted pulse sequence with a non-Cartesian BLADE trajectory (TGSE BLADE) can eliminate image artifacts and distortion with clinically acceptable scan times. This process has the potential to overcome the shortcomings of current diffusion-weighted imaging (DWI) techniques, especially in the sinonasal region. Purpose: To investigate the feasibility of TGSE BLADE in the assessment of sinonasal lesions and compare the quality of TGSE BLADE with RESOLVE images both qualitatively and quantitatively. Material and Methods: A total of 36 patients with sinonasal lesions were included in this prospective study. DW images acquired using TGSE BLADE and RESOLVE were performed with the same acquisition time. Two independent observers evaluated the qualitative parameters (overall image quality, lesion visibility, and geometric distortion) and quantitative parameters (geometric distortion ratio [GDR], signal-to-noise ratio [SNR], contrast, contrast-to-noise ratio [CNR], and apparent diffusion coefficient [ADC] value) of the two sequences. Results: Qualitative assessment revealed that TGSE BLADE exhibited higher overall image quality ( P < 0.001) and lesion visibility ( P < 0.001) and less geometric distortion ( P < 0.001) than RESOLVE. Quantitative assessment showed that TGSE BLADE images exhibited higher contrast ( P < 0.001) and CNR ( P < 0.001) and lower GDR ( P < 0.05) and SNR ( P < 0.001) than RESOLVE images. The ADC value of TGSE BLADE was significantly lower than that of RESOLVE ( P < 0.05). Conclusion: TGSE BLADE can reduce susceptibility artifacts and geometric distortion more than RESOLVE and appears to be a promising diffusion imaging sequence for the assessment of sinonasal lesions.